Correction of Thrombocytopenia before Elective Surgery / Invasive Procedures in Patients with Liver Cirrhosis (Experts’ Agreement) - M. V. Maevskaya; M. Yu. Nadinskaia; E. N. Bessonova; N. I. Geyvandova; M. S. Zharkova; E. A. Kitsenko; N. V. Korochanskaya; I. A. Kurkina; A. L. Melikyan; V. G. Morozov; Yu. V. Khoronko; T. A. Deeva; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Introduction. As a result of portal hypertension (sequestration of platelets in an enlarged spleen) and liver failure (decreased production of thrombopoietin in the liver) in liver cirrhosis, thrombocytopenia develops, which is associated with the risk of periprocedural/perioperative bleeding complications. There are still unresolved questions regarding risk stratification of bleeding complications, the prognostic role of thrombocytopenia, as well as the need for treatment of thrombocytopenia and its methods.Materials and methods. The Russian Scientific Liver Society selected a panel of experts in the field of therapeutic and surgical hepatology, hematology, transfusion medicine to make reasoned statements and recommendations on the issue of treatment of thrombocytopenia before elective surgery / invasive procedures in patients with liver cirrhosis.Results. Relevant clinical issues were determined based on the PICO principle (patient or population, intervention, comparison, outcome). The Delphi panel made five questions and gave reasoned answers, framed as ‘clinical practice recommendations and statements’ with evidence-based comments. The questions and statements were based on the results of search and critical analysis of medical literature using keywords in English- and Russian-language databases. The formulated questions could be combined into four categories: bleeding risk stratification, the prognostic value of thrombocytopenia, the necessity and methods of thrombocytopenia drug correction, and bleeding risk reduction.Conclusions. The results of experts' work are directly related to high-quality management of patients with liver cirrhosis and thrombocytopenia, who have scheduled invasive procedures/surgery. Thus, this recommendations and statements can be used in clinical practice.